Kesan Penggunaan Hitungan Astronomi Dan Alatan Moden Dalam Cerapan Hilal Di Malaysia: Satu Penelitian - Abdul Niri, Mohammaddin; Mohd Nawawi, Mohd Saiful Anwar; Ismail, Khadijah; Abdul Wahab, Raihana; Ahmad Zaki, Nurul Huda (Jurnal Fiqh, 2012)
Science and technology (S&T) are necessary as a tool to help Islamic jurists understand related issues explicitly. On the crescent visibility issue, the implementation of S&T through astronomical calculation and instrumentation is still debated, some accept while others reject. Therefore, this paper will examine the effects arising from the implementation of S&T. The crescent visibility data for 2010 were analysed to examine the effects. The results showed that S&T can strengthen the method of rukyah (observation), thereby overcoming the indecision and reducing the fallibility from the observation and the witness. The issued juristic result can also be made accurately and proven scientifically. Without S&T, the result might be supported by weak testimonial, even though the witness is qualified.